Analisis Price Earning Ratio (PER) dalam Pengambilan Keputusan Investasi Saham Perbankan: - Acep Samsudin; Rusdi Hidayat; Citra Nia Ramadhani; Silvia Nur Safitri; Vanny Rahma Yulianti; Thomas Ferdiansyah; Muhammad Falihul Royhan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
A method commonly used to assess the stock price of a company based on its ability to generate net income is known as a ratio. The net profit in question is the Earning Per Share itself. while the Net Profit in a company divided by the number of outstanding shares is the meaning of Earning Per Share, Earning Per Share is a reflection of the net income of the shareholders in the company. From the results of research on the consensus stock price itself within 12 months using the PER calculation method, researchers have chosen stocks that will be a priority in making investment decisions with the lowest Price Earning Ratio (PER) value, PT Bank Negara Indonesia (BBNI) shares. with a PER of 9.46X and a potential price increase of 27.03% based on consensus prices. Keyword: Price Earning Ratio (PER), Earning Per Share (EPS), Stock Price